Adaptação da Escala de Inteligência Emocional de Wong e Law (WLEIS) e análise da sua estrutura factorial e fiabilidade numa amostra portuguesa - Rodrigues, Nuno (2011)
The construct of emotional intelligence have generated important research efforts in the WOP domain in the last years. Different approaches of this construct have been proposed and as a consequence different measures were developed. The WLEIS have been used in a number of studies carried out in this domain, emerging as a measure of emotional intelligence with appropriate psychometric characteristics. This study aimed to adapt this measure for the Portuguese population and analyze the factor structure and reliability of the Portuguese version of this scale in a sample of software engineers. The results of a confirmatory analysis support the fit of the data to the tetra-factorial structure of the original measure and the obtained reliabilities supported the psychometric properties of this measure.